Overview of Student Skills in Phantom-Based Contraceptive Device Installation - Sri Utami Asmarani Sri Utami; Ayu Endang Purwati; Sandriani Sandriani (Yayasan Inspirasi El Burhani, 2022)
Introduction: The laboratory is a very important element as a means in various scientific activities. The results of the study explain that practicum activities are one of the efforts that can be made to improve science process skills and students' critical thinking skills. Aim: This study aims to describe the skills of students in the installation of a phantom-based intrauterine device (IUD) in the practical course Women's Health and Family Planning. Method: This research is a descriptive observational study. The population in this study were all level 2 students of the D3 Midwifery study program. The sampling technique used a total sampling of 38 people. The instrument used in this study was a checklist for the installation of an intrauterine device. Result: The results showed that students who were able to install phantom-based intrauterine devices were more than 26 people (68.4%), while students who were proficient at installing phantom-based intrauterine devices were fewer, namely 12 people (31.6%). and students who need improvement in installing contraceptives in the womb are 0 people (0%). Conclusion: Overall, the description of students' skills in installing phantom-based intrauterine devices is in the capable category with a percentage of 68.4%. It is hoped that in the next practicum students will be proficient in installing phantom-based intrauterine devices.